A influência do Projeto Jardim de Gente na reinvenção do cotidiano dos jovens do Bom Jardim: um estudo de caso no curso de Prática de Conjunto - Ferreira, Gabriel Nunes Lopes (2015)
This paper discusses music education in non-formal spaces of education and how these spaces contribute to the musical education on the outskirts of Fortaleza. The project aims the understanding of the importance of music courses held by the Project Jardim de Gente (Garden of People) through the students’ perspective. The project is developed in the neighborhood of Bom Jardim, the premises of the Bom Jardim Cultural Center. The main theoretical framework of the research is based on Bourdieu, with his studies on power games and social classes; Certeau, with his research on everyday life; and Koellreutter, with its proposal for Music Education. As a methodological approach, a case study in the course of Joint Practice was made. Ten students who participated in the course in the period 2010 to 2013 were chosen and interviewed. In addition to this, course planning and the Pedagogical Political Project of Garden of People (Projeto Político Pedagógico do Jardim de Gente) were used as sources of evidence, the latter was developed collectively with the participation of the community, students, teachers and coordination of the Project. Thus, the Practice course comes as perceptions of space changes with respect to musical practice and also in relation to daily students activities. According to the results, the project appears as a democratization of musical knowledge, reinventing the daily lives of its attendees.